The role of telenursing in the management of Diabetes Type 1: A randomized controlled trial. (April 2018) - Kotsani, Konstantia; Antonopoulou, Vasiliki; Kountouri, Aikaterini; Grammatiki, Maria; Rapti, Eleni; Karras, Spyridon; Trakatelli, Christina; Tsaklis, Panagiotis; Kazakos, Kiriakos; Kotsa, Kalliopi
Abstract: Background: Diabetes Mellitus type 1 (T1DM) is a chronic disease that requires patients' self-monitoring and self-management to achieve glucose targets and prevent complications. Telenursing implicates technology in the interaction of a specialized nurse with patients with chronic diseases in order to provide personalized care and support. Objective: To evaluate the effect of telenursing on T1DM patients' compliance with glucose self-monitoring and glycemic control. Design: Randomized controlled study. Settings: Outpatient Department of Diabetes, Endocrinology and Metabolism of a University Hospital in Northern Greece. Methods: Ninety-four T1DM patients were recruited and randomized in two groups by a random number generator. The intervention group (N = 48) was provided with telenursing services. A specialized nurse made a weekly contact via telephone motivating patients to frequently measure blood glucose and adopt a healthy lifestyle. The control group (N = 46) received standard diabetes advice and care in the clinic. The primary outcome was the effect of the intervention in glucose control and glucose variability. The secondary outcome was the effect on frequency of self-monitoring. SPSS 20.0 was used for data analysis. Results: The two groups did not differ in age, sex, physical activity or initial HbA1c. In the intervention group, blood glucose significantly decreased at the end of the study in all predefined measurements, compared to control group: morning (93.18 ± 13.30 mg/dl vs. 105.17 ± 13.74 mg/dl, p < 0.005), pre-prandial (114.76 ± 9.54 mg/dl vs. 120.84 ± 4.05 mg/dl, p < 0.005), post-prandial (193.35 ± 25.36 mg/dl vs. 207.84 ± 18.80 mg/dl, p < 0.005), and HbA1c decreased significantly over time in the intervention group (8.3 ± 0.6% at the beginning of the study vs. 7.8 ± 1% at the end of the study, p = 0.03). In the intervention group there were also fewer omitted glucose measurements than in the control group. Conclusions: Patients in the intervention group achieved better glucose control and more frequent self-monitoring than patients in routine care in the clinic. The findings of our study indicate that telenursing can motivate T1DM patients to better control their disease.